Communicable Diseases Surveillance: CDI volume 25 issue 1 (2001) - No author listed (Communicable Diseases Intelligence, 2001)
Communicable diseases surveillance highlights for 4th quarter, 2000 (gastrointestinal illness, chlamydial infection, vaccine preventable diseases, legionellosis, meningococcal infections, vectorborne diseases), and surveillance outcomes from several reporting series as follows: Outbreak report: Measles cluster in south-eastern Sydney with transmission in a general practice waiting room; National Notifiable Diseases Surveillance System tables, 1 October to 31 December 2000; Laboratory Serology and Virology Reporting Scheme tables, 1 October to 31 December 2000; Australian Sentinel Practice Research Network report tables, weeks 40-43 to 48-52, 2000; Australian encephalitis: chicken surveillance program, reporting period November and December 2000; Rotavirus surveillance, reporting period June to November 2000; HIV and AIDS surveillance, reporting period 1 to 31 August 2000, assessed as at 30 November 2000; Australian childhood immunisation coverage, 1 July to 30 September 2000 cohort, assessed as at 31 December 2000.